Master's degree in Advanced Practice Nursing for northwestern México by the University of Sonora - Peralta-Peña, Sandra Lidia (Universidad de Sonora, 2023)
Advanced Practice Nursing (APN), a trend that began approximately 60 years ago in the United States and Canada as a strategy to increase access to health services and health coverage (1,2); to reduce health costs (3) and mortality (4); shows an increase in its use in the world's healthcare systems.